The Values of Character Education in "Terempoh" Silaturahmi Tradition of Malay Society in Sintang City - Ropita Dewi Sartika; Saefur Rochmat; Zulkarnain Zulkarnain (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The Terempoh tradition is a hereditary tradition of the Sintang Malay community. This tradition is still being carried out today. The Terempoh tradition is usually carried out during Eid al-Fitr and Eid al-Adha as a tradition of gathering the Sintang Malay community. Even though it is a long tradition, this Terempoh Tradition contains character values which when properly applied in education will provide many lessons and benefits to students in social life. The purpose of this article is to describe the Terempoh as a Sintang Malay Community Gathering Tradition. The formulation of the problem / purpose of writing this article is to describe the Terempoh as a tradition of hospitality for the Malay community in the city of Sintang and the values contained in this tradition which can be used as lessons and guidelines for community life for the people of the city of Sintang. The method used in writing this article is qualitative. Meanwhile, the data collection techniques used in the writing of this article were interviews and literature studies.